KADAR ALPHA FETOPROTEIN (AFP) DENGAN PROFIL HbsAg PADA PASIEN KARSINOMA HEPATOSELULER DI RSUD PROF. DR. MARGONO SOEKARJO: SEBUAH STUDI CROSS SECTIONAL - Yudiananda, Domas Shifa; Sulistyo, Hidayat; Wijayana, Kamal Agung (Medical and Health Journal, 2024)
Background: Hepatocellular carcinoma is 10-20% of all liver diseases in Indonesia. Detect the emergence of hepatocellular carcinoma in the early phase are needed, especially in patients with high risk, such as chronic hepatitis and cirrhosis of the liver by performing regular investigations (USG, CT Scan) and laboratory examinations (AFP, PIVKA II). Aim: To determine the correlation between AFP levels and HbsAg profile in Hepatocellular Carcinoma patients at Regional Public Hospital of Prof. Dr. Margono Soekarjo. Methods: The research method was analytic observational with cross sectional approach. This research uses samples from January-December in 2020. The sampling method of this research is Total sampling. Retrospective data retrieval of secondary data in the form of medical records of the research sample. The research subjects were Hepatocellular Carcinoma patients at Prof. Dr. Margono Soekarjo, totaling 30 people. Result: The mean of people with hepatocarcinoma was 22 men with a percentage of 73.33%, while 8 people were female with a percentage of 26.67%. The mean age of the subjects of this study was 49.5 years. Subjects who had reactive results on HBsAg examination were 21 people with a percentage of 70%. The mean AFP level of the subjects was 17379.37 with a standard deviation of 25968.78. Results of the Fisher test for the correlation between AFP and HbsAg profile in hepatocellular carcinoma patients had a significance value of 0.032 (p <0.05). Conclution: that there is a correlation between AFP levels and HBsAg profile in Hepatocellular Carcinoma patients at Regional Public Hospital Prof. Dr. Margono Soekarjo.